Política fiscal nos estados brasileiros e a lei de responsabilidade fiscal: uma análise do tipo de ajuste e da composição do gasto público - Semeghini, Uirá Sorbo (2011)
This study analyzes the evolution of fiscal policy of Brazilian states between 1986 and 2008, a period in which there was a significant fiscal adjustment in Brazil and an attempt to identify the type of adjustment practiced by the states, designed in accordance with the theoretical reference known as 'expectational vision of fiscal policy'. In parallel, the study analyzes whether the evolutionary goals of the fiscal policy, as defined by the Law of Fiscal Responsibility, we met during the process of adjustment. Accordingly, the purpose of this study is to contribute to the debate around Brazilian public finances, and especially to the financial analysis of sub-national governments, and it aims to highlight the conduct of the public accounts of Brazilian States during the proposed period. The study is organized in three chapters. In the first chapter, the evolution of legal and institutional initiatives that have influenced and determined a new fiscal stance for the Brazilian states is analyzed. Chapter II details the theoretical reference that has become known in literature as the 'expectational vision of fiscal policy', which suggests that certain fiscal adjustments may have expansionist effects on the level of economic activity. Chapter III attempts to analyze the accounts of the States in the indicated periods in order to identify the type of fiscal adjustment practiced. The purpose is to analyze the composition of the adjustments practiced, their effects on the State accounts and finally to identify the type of adjustment practiced. In parallel, the indicators imposed by the Law of Fiscal Responsibility are analyzed in order to ascertain whether they are being accomplished by the states.